Photodynamic-therapy and chemotherapy of TPBC-PEG nanoplatform encapsulated triptolide synergistically inhibit primary osteosarcoma growth and pulmonary metastasis by activating HIPPO signaling - Junli Chang; Wenyi Wang; Fulai Zhao; Xingyuan Sun; Suxia Guo; Chujie Zhou; Peng Zhao; Junjie Tong; Weian Zhang; Yanping Yang (Materials & Design)
Osteosarcoma is the most common bone malignancy in children and adolescents with a less than 30% overall survival rate for those with metastatic disease, particularly pulmonary metastases. Drug resistance hinders the effectiveness of current chemotherapies, making osteosarcoma a leading cause of mortality and an urgent requirement of new therapeutics in this population. Here, we developed a triptolide (TP)-loaded, pH-responsive and near-infrared light-activated nanoplatform (TP-TPBC-PEG) with photodynamic therapy (PDT) to target osteosarcoma cells both in vitro and in vivo. Our results demonstrated that PDT and chemotherapy of TP-TPBC-PEG synergistically reduced cell viability, colony proliferation, migration, and invasion in vitro, and inhibited osteosarcoma growth and pulmonary metastasis in vivo which the nano-micelles were intravenously injected to intratibia injection induced osteosarcoma mouse models, showing enhanced osteosarcoma cell killing by nanoparticle inflating in response to acidic endosomal pH and sensitized osteosarcoma cells to TP chemotherapy. Importantly, the nano-micelles did not exhibit organ toxicity in vivo. Dual-luciferase reporter gene and nuclear/ cytoplasm protein expression assays identified the involvement of HIPPO signaling pathway in mediating these effects. Overall, our study provides a promising therapeutic approach for treating primary osteosarcoma and preventing pulmonary metastases by activating the HIPPO signaling pathway.